System monitoring of solar power plant using NODE MCU ESP8266 based on IOT - Limbong, Fitrah Hasan; Taufiq, T; Bintoro, A (Geuthèë Institute, 2024)
Solar Power Plants (PLTS) have become a very popular energy source and have great potential in reducing dependence on fossil energy sources. The Node MCU ESP8266 is one type of microcontroller that is highly popular in the development of IoT projects. In generating electrical energy, the Internet of Things (IoT) technology has rapidly developed and become one of the most popular technologies in the field of electrical energy. With a PLTS monitoring system using a website, users can monitor the performance of the PLTS in real-time. Solar panels or solar cells are equipment modules that can convert solar energy into electrical energy with DC current. Monitoring is the process of systematically and continuously collecting and analyzing information based on predetermined indicators of activities/programs, allowing corrective actions to be taken for the improvement of the program/activity. The researchers will also discuss the importance of monitoring PLTS, as well as the potential of IoT technology to improve the efficiency and quality of electrical energy production. The website is used to operate IoT principles designed for fast and easy real-time reading. Functional testing is divided into three parts: voltage sensor testing, ACS712 current sensor testing, and NodeMCU testing. The electrical parameters to be measured include output current and output voltage. The PLTS monitoring system device, also known as the Box Panel, has been designed, built, and tested. The testing phase is carried out by conducting functional tests on the system to determine the success rate and accuracy of the device. Once the box panel functions properly, it can be used to monitor the output of the PLTS, and the measurement results will be displayed on the website that has been created.